Obstetric and perinatal complications due to SARS-CoV-2 in a referral hospital in the Huancavelica region - Aparicio-Ponce, Jorge Renato (2022)
Objective. To determine obstetric and perinatal complications in SARS-CoV-2pregnant women at the Departmental Hospital of Huancavelica. Methods.A descriptive, with documentary analysis of the medical records of pregnant women who completed their pregnancy at the institution and of the newborns. A validated data collection form was used. Admitted pregnant women were positivefor SARS-CoV-2 with a laboratory test. Descriptive statistics were performed,establishing frequencies, averages and percentages. The study is included in the National Health Research Registry. Results. A total of 148 pregnant women wereadmitted, average age 27 years. A 53.4 % were controlled. The majority, 54.1 % (80), were multiparous. The diagnosis of SARS-CoV-2 was made by detection of antibodies (85.6 %). A total of 90.5 % (134/148) were asymptomatic. SARS-Cov-2pneumonia was recorded in 8 cases. Abortion accounted for 16.2 %. The majority, 86.5 % (109), were of term gestational age. The route of delivery was similar for cesarean/vaginal delivery (51.6 %/48.4 %). There were no obstetric complications (65.5 %). The most frequent complications were: premature rupture of membranes and preeclampsia. The newborns had adequate Apgar scores (94.4 % at one minute/96.8 % at fve minutes). Preterm infants accounted for 11.9 %. Most of them had adequate weight (86.5 %). There were no SARS Cov-2 positive neonates.Conclusions. Most of the pregnant women attended at the DepartmentalHospital, positive for SARS-CoV-2, were asymptomatic. The most frequent obstetric complications were premature rupture of membranes and preeclampsia. The perinatal outcomes of the newborns were adequate in the great majority